PEDAGOGICAL ACTIVITY TOOLS IN ELECTRONIC ENVIRONMENT - T. N. Noskova; T. B. Pavlova; O. V. Yakovleva (Moscow Polytechnic University, 2017)
The paper introduces the concept of "pedagogical ICT tools", which makes it possible to identify the necessary professional teacher activity transformations in electronic educational environment. The paper presents the typology of tools and describes their features. The introduction of the concept allows revealing the range of opportunities and transformations of the university teachers' activity in electronic environment. Experimental data on the use of pedagogical ICT tools by teachers of European universities was obtained during the implementation ofthe European IRNet project.